Plastics in the environment and trends for the future - Silva, Welleson Roberto de Lira; Lima, Júlia Guedes de; Campos-Takaki , Galba Maria (Seven Editora, 2023)
The studies carried out are about the first molecules, classification, properties and environmental problems caused by the rampant disposal of plastics. In this context, with the increase in the unbridled consumption of plastic, which has been contributing to major contamination in all environments, mostly culminating in the oceans. It should be noted that polypropylene is one of the most used polymers in the manufacture of flexible plastic packaging and the accumulation of these materials in the environment, especially in the oceans, has been causing several negative impacts on the planet’s biodiversity. An alternative to the problems caused by the improper disposal of this waste would be the replacement of traditional plastics with biodegradable and compostable polymers from renewable sources whose life cycle tends to be less polluting, since, under favorable conditions, they degrade in biologically active environments, not producing toxic waste for the environment. Therefore, it becomes necessary to implement legislations that favor the use of bioplastics over conventional plastics and the changes in consumer behavior that drive the market for biopolymers. The problems of plastics in the environment and in human health are presented as a function of the understanding of the concerns, in addition to a look at priorities, challenges, opportunities that bring benefits with the application of plastics in the future. However, about the use and disposal that have been increasing, and the need to recycle and reverse this trend, so that they can be considered end-of-life materials, as valuable raw materials for new production, instead of waste. DOI:https://doi.org/10.56238/innovhealthknow-039